Pelatihan Pemanfaatan Buku KIA dengan Metode Mentorship Learning pada Kader di Wilayah Kerja Puskesmas Syamtalira Bayu - Nurmila, Nurmila; Elizar, Elizar; Putri, Hendrika Wijaya Kartini (Jurnal Abdimas Kesehatan (JAK), 2025)
Maternal and child health (MCH) services require effective communication, information, and education (CIE) media supported by a structured recording system. The Maternal and Child Health Book (MCH Book) has been established by the Ministry of Health of the Republic of Indonesia as the sole official tool for documenting MCH services nationwide. However, its utilization remains suboptimal, mainly due to the limited knowledge and skills of posyandu cadres. This community service program was conducted in the working area of Syamtalira Bayu Primary Health Center with the objective of enhancing cadres’ knowledge and skills in using and documenting the MCH Book. The intervention included socialization, pre-test, education and training sessions, group discussions, post-test, and mentoring. Evaluation results showed a considerable improvement in cadres’ understanding and ability to use the MCH Book effectively. Cadres actively participated in all activities and demonstrated the application of acquired knowledge in posyandu services. This program highlights the essential role of cadres in promoting the utilization of the MCH Book among pregnant women, breastfeeding mothers, and mothers with infants and toddlers. Strengthening cadres’ capacity contributes to improved monitoring of maternal health as well as children’s growth and development at the community level